2016
DOI: 10.1016/j.autrev.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in inflammatory arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic chronic inflammatory disease characterized by extensive synovitis resulting in erosions of articular cartilage and marginal bone with joint destruction. The lack of immunological tolerance in RA represents the first step toward the development of autoimmunity. Susceptible individuals, under the influence of environmental factors, such as tobacco smoke, and silica exposure, develop autoimmune phenomena that result in the presence of autoantibodies. HLA and non-HLA haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 180 publications
(216 reference statements)
2
60
0
5
Order By: Relevance
“…Importantly, we found that the levels of both anti–ADAMTS‐L5 and anti–LL‐37 autoantibodies were significantly elevated in patients with PsA compared to non‐PsA controls, suggesting that these molecules may be involved in the pathogenesis of PsA. This is consistent with previous findings showing that autoantibodies may be associated with PsA . Furthermore, the autoantibodies against ADAMTS‐L5 or LL‐37 could be used as biomarkers to discriminate PsA from non‐PsA.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, we found that the levels of both anti–ADAMTS‐L5 and anti–LL‐37 autoantibodies were significantly elevated in patients with PsA compared to non‐PsA controls, suggesting that these molecules may be involved in the pathogenesis of PsA. This is consistent with previous findings showing that autoantibodies may be associated with PsA . Furthermore, the autoantibodies against ADAMTS‐L5 or LL‐37 could be used as biomarkers to discriminate PsA from non‐PsA.…”
Section: Discussionsupporting
confidence: 91%
“…This thinning might also be due to HCQ treatment or apoptosis of retinal ganglion cells induced by anti-Ro antibodies. It is well known that autoantibodies may exert a pathogenic role in autoinflammatory/autoimmune diseases [46, 47]. Data from the literature suggest that anti-Ro antibodies could play a role in mediating or potentiating vascular injury in the central nervous system [48].…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of RA involves components of innate and adaptive immunity (1). Although the pathogenesis of RA remains poorly understood, production of autoantibodies along with infiltration of synovial fluid and tissues by inflammatory cells have been identified as key events (2)(3)(4). Collageninduced arthritis (CIA) is a murine model that closely mimics RA (5).…”
mentioning
confidence: 99%